Alarming attitudes and misconceptions regarding psychiatry - Muhammad Wasim; Mahad Mirza Baig; Dua Bushra (Journal of the Pakistan Medical Association, 2023)
Dear Respected Editor, we would like to highlight the level of neglect concerning to knowledge of psychiatry especially in developing countries like Pakistan. Even while crafting this correspondence, our search for literature investigating the state of knowledge about psychiatry produced a surprisingly low number of results (aside from surveys of general mental health). Of the few which we could find, an alarming lack of knowledge was evident. One such survey-based investigation found that most medical school student respondents believed the aetiology of psychiatric illness to be from “excess emotions,” and an astonishing 27 out of the 164 medical students polled believed the etiology to be either “past sins” or “evil spirits.” 1 Other publications in recent years have mostly attempted to address prevailing myths present in society through reviews seeking to dispel misconceptions.2 Therefore, the leaders in the field of psychiatry have to optimize theirpublic outreach methods to renovate this discipline’s public image. While it is important to consider the specific cultural influences that have had a hand in shaping stigmas and their consequences, looking towards successful campaigns abroad can be s an important source of inspiration when forming a similar approach to implement in Pakistan. Examples of successful psychiatric awareness campaigns can be found in countries such as the United States and Germany.3 Moreover, it is important to remember that to capture the esteem of our society’s most influential figures, more scientific rigour must be applied to the field of psychiatry. Hence, more publications should be made which document the successful treatment and various presentations of psychiatric illnesses. A consistently renewing wealth of scientific literature to demonstrate the patterns which have emerged over the last few centuries in psychiatry are essential for dispelling misinformation.4 Despite significant progress over the last few years, psychiatry shall continue to prove challenging to promote in more mainstream sources of information unless existing social barriers are addressed. The reverse seems equally plausible in that pre-existing social stigmas tend to prevent patients from seeking care or disclosing case information to providers. Therefore, both social reform and an emphasis on scientific exploration are necessary to ensure the continued growth of confidence in psychiatric practice.